ANALISIS RISIKO KEKERINGAN DI KABUPATEN BANTUL PROVINSI D.I. YOGYAKARTA - Annisa Mu'awanah Sukmawati; Puji Utomo (Jurnal Planologi, 2021)
Bantul Regency is a district in Yogyakarta Province which has geographic, geological, hydrological, and demographic characteristics that are likely to cause drought. Drought event in Bantul Regency may have significant impacts on various aspects in line with the characteristics of drought impacts which are complex and cross-sectoral. This study addresses to analyze the level of risk of drought with observation units in 75 villages in the Bantul Regency. The risk analysis was carried out by comparing the time period of the 10 years, i.e. 2008 and 2018 to observe the shift of risk areas of drought in Bantul Regency. The research was conducted using quantitative research methods with quantitative descriptive and mapping analysis. The analysis steps are drought hazard analysis, vulnerability analysis, and drought risk analysis. The analysis shows that during the last 10 years, Kabupaten Bantul has been experiencing an increasing number of villages classified as high risk of drought, both in urban and rural areas. In 2008 there were 15 villages (20%) and increased to 21 villages (28%) in 2018 that were classified as very very high level. Meanwhile, in 2008 there were 30 villages (40%) in 2008 and increased to 32 villages (42.7%) in 2018 that were classified as very high level. It caused by the increasing probability of drought as well as vulnerability. The analysis results can be used as input for stakeholders to take mitigation and anticipation actions to reduce the impact of drought based on the spatial characteristics of the risk areas.